A systematic literature review of university student enrolment from 2020 to 2023 / Li Yan ... [et al.] - Yan, Li; Swaran Singh, Charanjit Kaur; Junjie, Luo; Wong, Wei Lun; Daoyuan, Shen (Universiti Teknologi MARA, 2024)
This article undertakes a systematic literature review, employing the PRISMA method, to analyse university student enrolment from 2020 to 2023, a period significantly influenced by the COVID-19 pandemic. It is guided by key research questions: i)What theories or conceptual paradigms underpin the study?, ii) What variables intricately interface with the nuanced landscape of university student enrolment?, iii) Where is the designated research setting?, iv) What are the tools/approaches/models used for data analysis? and v) What are the main findings about student enrolment?. Employing a stringent PRISMA methodology, 17 articles were meticulously selected. These articles were subjected to qualitative appraisal based on predefined criteria, ensuring a focus on high-quality, relevant studies. The findings from these articles highlight significant themes: the rapid transition to online learning, the impact of socioeconomic factors on education access, trends towards internationalisation, the role of data analytics in enrollment management, the importance of the quality learning experience, and the influence of institutional branding on student recruitment. The findings suggest profound implications for higher education stakeholders. Firstly, the necessity for educational institutions to adapt to digital pedagogies is underscored. Secondly, addressing socioeconomic disparities in education access emerges as a critical concern. Thirdly, the increasing emphasis on global engagement strategies in university education is highlighted. Additionally, the role of data analytics in shaping recruitment and retention strategies is emphasised, along with the importance of comprehensive learning experiences and effective institutional branding. In conclusion, this review provides a nuanced understanding of the complex dynamics influencing university student enrolment during a period of global upheaval. It offers valuable insights for academic leaders, policymakers, and higher education administrators, stressing the need for adaptive, inclusive, and forward-looking approaches in higher education.